2016
DOI: 10.1021/acs.jpcb.6b02340
|View full text |Cite
|
Sign up to set email alerts
|

Water Structure at the Lipid Multibilayer Surface: Anionic Versus Cationic Head Group Effects

Abstract: Membrane water interface is a potential reaction site for many biochemical reactions. Therefore, a molecular level understanding of water structure and dynamics that strongly depend on the chemical structure of lipid is prerequisite for elucidating the role of water in biological reactions on membrane surface. Recently, we carried out femtosecond infrared pump-probe studies of water structure and dynamics at multibilayer surfaces of zwitterionic phosphatidylcholine-analogue lipid ( J. Phys. Chem. Lett. 2016 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Ultrafast vibrational spectroscopy has been extensively applied to study the water hydrogen-bond structure and dynamics in complex biological environments, including lipid membranes, either through direct measurement of the interfacial OH bonds through surface-specific measurements such as sum-frequency generation (SFG) or by probing of the vibrational modes of the lipid headgroups themselves. These studies showed that headgroup hydration environments are heterogeneous, containing a balance between tightly bound configurations and more labile molecules. , Despite being preferentially excluded from the interface, DMSO disrupts the interfacial environment by reducing lipid–lipid repulsion, as evidenced by the increasing lipid packing density and acyl melting points. However, there are many seemingly contradictory observations. In bulk solution, dehydration is typically accompanied by a slowdown of H-bond dynamics as water molecules near the hydrophilic headgroup become more tightly bound. , However, interfacial water diffusion becomes faster with the addition of DMSO.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast vibrational spectroscopy has been extensively applied to study the water hydrogen-bond structure and dynamics in complex biological environments, including lipid membranes, either through direct measurement of the interfacial OH bonds through surface-specific measurements such as sum-frequency generation (SFG) or by probing of the vibrational modes of the lipid headgroups themselves. These studies showed that headgroup hydration environments are heterogeneous, containing a balance between tightly bound configurations and more labile molecules. , Despite being preferentially excluded from the interface, DMSO disrupts the interfacial environment by reducing lipid–lipid repulsion, as evidenced by the increasing lipid packing density and acyl melting points. However, there are many seemingly contradictory observations. In bulk solution, dehydration is typically accompanied by a slowdown of H-bond dynamics as water molecules near the hydrophilic headgroup become more tightly bound. , However, interfacial water diffusion becomes faster with the addition of DMSO.…”
Section: Introductionmentioning
confidence: 99%
“…In parts b and c of Figure S12, the vibrational relaxation dynamics of the OD stretch of HOD at 2520 cm –1 in pure water are directly compared with those of HOD on biocompatible polymer surfaces. Table shows that the vibrational lifetime of the OD stretch of HOD in pure water is 1.76 ps, which is in excellent agreement with the previously reported value . It should be noted that 20 vol % HOD is used in this study, which shows the same vibrational relaxation time as 5 vol % HOD usually used for time-resolved IR experiments for water.…”
mentioning
confidence: 55%
“…Table 1 shows that the vibrational lifetime of the OD stretch of HOD in pure water is 1.76 ps, which is in excellent agreement with the previously reported value. 32 It should be noted that 20 vol % HOD is used in this study, which shows the same vibrational relaxation time as 5 vol % HOD usually used for time-resolved IR experiments for water. The vibrational lifetime of the fast 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we address the question about how the water H-bonding structure and the extent of hydration of block copolymer subunits change with temperature and P123 concentration in aqueous solutions by using femtosecond IR PP technique, which enables direct measurements of vibrational and rotational dynamics of water molecules. The OD stretch mode of HDO has long been considered an excellent IR probe for water and has been widely used in studying ultrafast water H-bonding making and breaking dynamics in a number of aqueous solutions containing micelles, amphiphilic mixtures, , reverse micelles, polymers, , lipid multibilayers, ,,,, lamella, and so forth. , In this Letter, we present the polarization-controlled IR PP results for aqueous P123 solutions at two different concentrations (1 and 23 wt %) with varying temperature to study the phase transitions from unimers to micelles and from micelles to the gel phase (see Figure b,c).…”
mentioning
confidence: 99%